2007
DOI: 10.1176/appi.ajp.164.7.1035
|View full text |Cite
|
Sign up to set email alerts
|

Columbia Classification Algorithm of Suicide Assessment (C-CASA): Classification of Suicidal Events in the FDA’s Pediatric Suicidal Risk Analysis of Antidepressants

Abstract: Objective-To evaluate the link between antidepressants and suicidal behavior and ideation (suicidality) in youth, adverse events from pediatric clinical trials were classified in order to identify suicidal events. The authors describe the Columbia Classification Algorithm for Suicide Assessment (C-CASA), a standardized suicidal rating system that provided data for the pediatric suicidal risk analysis of antide-pressants conducted by the Food and Drug Administration (FDA).Method-Adverse events (N=427) from 25 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
245
0
6

Year Published

2009
2009
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 489 publications
(255 citation statements)
references
References 34 publications
3
245
0
6
Order By: Relevance
“…Later, the World Health Organization Regional Office for Europe (WHO/EURO), as part of their Multicentre Study of Parasuicide Attempts identified and proposed an unifying terminology (8). Nevertheless, no final consensus has been reached yet (12)(13)(14).…”
Section: Figure 1: Traffic Accidents Vs Suicides: Catalonia 1999-2013mentioning
confidence: 99%
“…Later, the World Health Organization Regional Office for Europe (WHO/EURO), as part of their Multicentre Study of Parasuicide Attempts identified and proposed an unifying terminology (8). Nevertheless, no final consensus has been reached yet (12)(13)(14).…”
Section: Figure 1: Traffic Accidents Vs Suicides: Catalonia 1999-2013mentioning
confidence: 99%
“…Items assessed included problems such as sleeping, irritability, hostility, aggression, restlessness/agitated/anxious/nervous, tremors, overly excited, emotional lability, disinhibition, and altered thinking, and nonsuicidal self injurious behavior. Suicidal ideation and behavior were monitored weekly using the Suicide Severity Rating Scale (SSRS) (Posner et al 2007). This is a twoitem scale that rates suicidal ideation on a 0 to 5 scale (no ideation to suicidal ideation with intent and a clear plan) and suicidal behavior on a 0 to 5 scale (no behavior to multiple attempts).…”
Section: September 2003mentioning
confidence: 99%
“…• Guideline 35,36,48 • Quasi/nonexperimental 64,68,69 • Quasi/nonexperimental [61][62][63][65][66][67] QI 4: Brief supportive counseling.…”
Section: Guideline Recommendationsmentioning
confidence: 99%
“…67 Standardized algorithms and screening tools to assess suicide risk in adolescents have been developed but their use is not widespread. 68,69 Practice Implications…”
Section: Rationale and Evidencementioning
confidence: 99%